Socio-cultural dynamics of technogenic civilisation: conceptual model by V. S. Stepin - Kolyadko, Ilya N. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The article discusses the features of the sociodynamics of technogenic civilisation in the context of radical socio-cultural transformations taking place at the present stage of human history. At the same time, the justified by academician V. S. Stepin’s concept, according to which the transformation of the foundations of social systems and its key areas (political-institutional, socio-economic, spiritual, etc.) is due, first of all, to the reinterpretation of the basic meanings of the worldview universals of culture, functioning in the public consciousness as schematisms that determine perception of the world, its understanding and experience by a person. At the same time, it is noted that modern civilisational changes are determined by many factors (economic, political, technological, etc.), but cultural factors occupy a central place among them. The development of the sciences of society and culture in the second half of the 20th – early 21st century quite clearly fixed the programming functions of culture in human activity. It is noted that there is no such area of activity, behaviour and communication of people, there are no such social states, structures, institutions that would arise, reproduce and change outside the influence of culture and outside the change in its foundations, explicated in worldview universals.
Keywords: culture; worldview universals; socio-cultural transformation; technogenic civilisation